Features of nickel alloy structure, conditions for crystallization and isolation of main and redundant phases during modification - Yu. O. Filippov; E. N. Eremin; D. A. Sedykh; O. V. Kropotin (Омский научный вестник)
The influence of modification of heat-resistant nickel-based alloys on the crystallization kinetics of alloys was established by the methods of thermal analysis. This effect is expressed in the increase in solidus temperature and, as a consequence, narrowing the crystallization range of the alloy, the increase in the growth rate of a solid solution, and change in the temperature of precipitation of eutectic and strengthening phases. As a result, the use of modification with refractory particles makes it possible to exert an additional effect on the structure and properties of nickel-based alloys without additional heat treatment.